Optimization of Bhabinkamtibmas Guidance in Preventing the Spread of Radical Terrorism Ideology in the Polresta Magelang Area - Prasetya, Peres (Advances in Police Science Research Journal, 2024)
This research aims to optimize the guidance of Bhabinkamtibmas (Police Community Officer) in preventing the spread of radical terrorist ideology in the Polresta Magelang area, as the spread of radicalism and terrorism poses a serious threat to the security and public order in Indonesia. Therefore, guidance by Bhabinkamtibmas is considered as an effective prevention effort in reducing and preventing the spread of radicalism and terrorism in society. This research uses a qualitative approach with field study, interviews, and document studies as methods. The analytical tools used are Crime Prevention theory and POAC Management theory. The concepts used include the concepts of Bhabinkamtibmas, the spread of Radicalism ideology, Counter-Radicalization concept, and Guidance and Counseling concept. The results show that the guidance provided by Bhabinkamtibmas in Polresta Magelang is already good, but it still needs to be improved by increasing the quality of members’ abilities in mastering Radical Terrorism material and increasing the quantity of guidance on Radical Terrorism, improving cooperation with relevant stakeholders, and improving the supporting infrastructure for guidance activities. Bhabinkamtibmas should have sufficient understanding of radical terrorist ideology and good communication skills with the community. In addition, appropriate and sustainable delivery strategies and support from various parties are needed to optimize the guidance of Bhabinkamtibmas in preventing the spread of radical terrorist ideology in the Polresta Magelang area. The guidance by Bhabinkamtibmas is expected to provide the correct understanding of Pancasila, UUD 1945, NKRI, and Bhinneka Tunggal Ika to the community and foster a spirit of tolerance and peace in the midst of diversity.